Hydrogels as artificial matrices for cell seeding in microfluidic devices. Issue 71 (8th December 2020) - Akther, Fahima; Little, Peter; Li, Zhiyong; Nguyen, Nam-Trung; Ta, Hang T.
Abstract : Hydrogel-based artificial scaffolds and its incorporation with microfluidic devices play a vital role in shifting in vitro models from two-dimensional (2D) cell culture to in vivo like three-dimensional (3D) cell culture Abstract : Hydrogel-based artificial scaffolds play a vital role in shifting in vitro models from two-dimensional (2D) cell culture to three-dimensional (3D) cell culture. Microfluidic 3D cell culture systems with a hydrogel matrix encourage biomedical researchers to replace in vivo models with 3D in vitro models with a cellular microenvironment that resembles physiological conditions with greater fidelity. Hydrogels can be designed as an artificial extracellular matrix scaffold for providing spatial orientation and promoting cellular interactions with surroundings. Selecting the appropriate hydrogels and their fabrication techniques are the key to mimic the in vivo mechanical environment. Moreover, combining a microfluidic technique with a hydrogel-based 3D cell culture system can create a complex and controlled microenvironment for the cells by placing small biosamples inside the microchannel. This paper provides an overview of the structural similarities of the hydrogels as an extracellular matrix (ECM), their classification and fabrication techniques as an ECM, and their use in microfluidic 3D cell culture systems. Finally, the paper presents the current challenges and future perspectives of using hydrogel scaffolds in microfluidic 3D cell culture systems.